New Ways of Mediating Learning: Investigating the implications of adopting open educational resources for tertiary education at an institution in the United Kingdom as compared to one in South Africa - Wilson, Tina (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
Access to education is not freely available to all. Open Educational Resources (OERs) have the potential to change the playing field in terms of an individual’s right to education. The Open University in the United Kingdom was founded almost forty years ago on the principle of ‘open’ access with no entry requirements necessary. The University develops innovative high quality multiple media distance-learning courses. In a new venture called OpenLearn, The Open University is making its course materials freely available worldwide on the Web as OERs ( see http://www.open.ac.uk/openlearn). How might other institutions make use of these distance-learning materials? The paper starts by discussing the different contexts wherein two institutions operate and the inequalities that exist between them. One institution is a university based in South Africa and the other is a college located in the United Kingdom. Both institutions, however, deliver distance-learning courses. The second part of the paper discusses preliminary findings when OERs are considered for tertiary education at these two institutions. The findings emphasise some of the opportunities and challenges that exist if these two institutions adopt OERs.